'We've been doing it your way long enough': Syncretism as a critical process. (September 2013) - Long, Susi; Volk, Dinah; Baines, Janice; Tisdale, Carmen
This article takes a new look at issues of marginalization and equity in literacy practice by focusing on the concept of syncretism and teachers' creation of opportunities for young children to draw on knowledge from multiple worlds as, together, they construct new texts, contexts and practices. Recognizing that the strengths and needs of too many students from minoritized communities are not being met, this piece draws attention to the importance of teachers' appreciation of syncretism as a powerful learning process for challenging discriminatory and exclusionary practices. Drawing on theories of syncretism, and critical and culturally relevant pedagogies, the authors introduce critical syncretism as a process in which teachers and children privilege traditions and practices typically marginalized in schools for the purpose of supporting achievement and broadening worldviews. The article provides examples from two primary-grade classrooms illustrating ways that the teachers made specific moves to change classroom power structures. Whereas White, middle-class, Standard English ways of knowing had been privileged by the school district's choice of instructional materials and recommendations for teaching practice, the teachers' new practices opened up possibilities for syncretism by embracing knowledge, languages, traditions and practices from students' homes, communities and African heritage, as well as from school.